The Selected Letters of Alice Meynell : Poet and Essayist. - Atkinson, Damian (Cambridge Scholars Publishing, 2013)
The Catholic convert and women of letters Alice Meynell (1847-1922) ranks as a sophisticated essayist and poet of the late Victorian period and the early twentieth century. She had the advantage of an educated father and a musical mother who spent much of their early time with the family visiting Europe, especially Italy. Alice's father was a friend of Dickens and her mother was admired by Dickens. Alice and her sister Elizabeth, later the famed artist Lady Butler, were educated privately and ...